Assessment of building maintenance management in Malaysia: Resolving using a solution diagram - Zawawi, Emma Marinie Ahmad; Kamaruzzaman, Syahrul Nizam; Ali, Azlan Shah; Sulaiman, Raha (Palgrave Macmillan UK, 2010)
This article examines the process of building maintenance and management in Malaysia with the aim of identifying factors causing poor maintenance in various types of buildings, and delivering a new improved process. The study focuses on the management of building maintenance, including setting up organisations, policies and quality standards. It makes extensive use of questionnaires and surveys as a means of data collection. The surveys cover all aspects of maintenance management in Malaysia, including occupant satisfaction, number of staff members and the strategies used in maintenance delivery. The framework of the process was then developed based on the outcome of the surveys. The process covers all major aspects such as management, staffing, training and regulation that are useful in managing maintenance sections. © 2010 Macmillan Publishers Ltd.